Manajemen Pelayanan Kesehatan dalam Perspeptif Islam Ibadah Ritual dan Kesehatan - Atila Sonmax; Sri Naharindah Ningsih; Crys Sena Puspitasari; Abul Ala Al Maududi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Prayer (shalat) is one of the fundamental pillars of Islam that serves not only as a means of worship and devotion to Allah SWT but also provides significant health benefits. This paper aims to explain the concept of ritual prayer in Islam, identify its health benefits, and analyze the relationship between prayer movements and the human body. The study employs a literature review method by examining relevant scientific publications and Islamic sources. The findings indicate that prayer has a holistic dimension encompassing physical, mental, spiritual, and social aspects. The various movements performed during prayer, such as takbiratul ihram, bowing (ruku’), prostration (sujud), and concluding salutation (salam), contribute to physical well-being by improving blood circulation, enhancing muscle and joint flexibility, and supporting cardiovascular health. From a psychological perspective, prayer helps reduce stress and anxiety while promoting inner peace through relaxation and mindfulness mechanisms. Furthermore, prayer strengthens spiritual health by fostering a closer relationship with Allah SWT, enhancing self-awareness, and creating a sense of balance in life. Therefore, prayer can be viewed as a holistic therapeutic practice that supports overall human health. Consistent and mindful performance of prayer is essential for maintaining physical, mental, and spiritual well-being.